The new extraordinary leader - Zenger, John H.; Folkman, Joe (McGraw Hill-Ascent Audio, 2019)
The landmark guide that built a generation of extraordinary leaders-fully updated and revised The definitive guide to 21st Century business leadership, The New Extraordinary Leader shook the foundations of leadership as we knew it when it was published in 2002. Since then, we have seen tectonic shifts in the world of business-and this revised and updated edition provides the data and insights you need to address them all. Jack Zenger and Jim Folkman's proprietary 360 feedback assessment of leaders in the real world-how they lead, what works, and what doesn't-provides the data that makes The Extraordinary Leader unique in a crowded field of such books. In this new edition, the authors deliver proven lessons based on feedback from 120,000 leaders from all corners of the globe. Inside, you'll find: * New chapters on leadership competencies, cross training, and self-development * New methods for getting inspired and empowered by demystifying leadership * New evidence on many ways leaders can singlehandedly boost innovation, employee engagement, profitability, and more * New research on the importance of developing strong leadership teams If you're looking to dramatically step up your leadership game, if you're looking for hard evidence of how to do it the right way, and if you're looking to drive measurable positive change in your organization-you need look no further. The New Extraordinary Leader, Third Edition delivers the information and insight you need to lead effectively in today's volatile, global economy.